Variation of moose (Alces alces) damage to Scots pine (Pinus sylvestris) in young forest stands - Olsson, Markus (2009)
Forest damage by moose is an important issue in Swedish forest and wildlife management. This study aimed at understanding the variation of moose (Alces alces) damage to Scots pine (Pinus sylvestris). By plots in twenty-five young forest stands damage level, damage variation and stand characteristics were investigated through a survey in April 2005. On average 2.4% of the main stems showed recent damage (i.e. from the preceding winter) and 29.4% of the main stems had previous damage (from before preceding winter). The variation of damage within stands was negatively correlated with damage level. Compared to damage level, damage variation showed inversely correlations to several stand characteristics. These relationships were interpreted as an interaction mainly between the unique characteristics of a stand and moose browsing pattern. Such interactions determine the damage level, which in turn determines the predominant level of damage variation. The risk of a pine to be browsed, if its neighbour is browsed, is significantly higher than what expected from random browsing. That risk decreased linearly with increasing distance to the browsed pine. The patterns revealed are discussed in terms of how to decrease the share of damaged main stems in future stands and how to improve surveys and predictions of damage levels in young pine stands. I studien undersöktes variationen av stamskador på tall (Pinus sylvestris) vilka orsakats av älgens (Alces alces) vinterbete i 0,5-3 m höga ungskogsbestånd. Genom provytor studerades beståndsegenskaper, skadenivåer och skadors variation inom 25 ungskogsbestånd. Dessutom undersöktes skaderiskerna på slumpmässigt valda tallar och deras närmsta tallgranne. I genomsnitt hade 2,4 % av huvudstammarna skador som uppkommit under den senaste vintern (färska skador) och 29,4 % av huvudstammarna hade skador som uppkommit vid tidigare tillfälle (äldre skador). Studien visar också att det beräkningssätt som används för att bestämma skadenivå har stor betydelse för utfallet. Skadornas ...